(untitled) (Zaporizhzhia Historical Review, 2021)
In the article is reflected the genesis of Zionist movement in Soviet Union in intermilitary period. The author points out the stages of the attack of soviet organs on Jewish organizations in the USSR, describes their maintenance and consequences for the Jewish population.